Mesoscopic light transport in nonlinear disordered media - Alfonso Nardi; Andrea Morandi; Romain Pierrat; Arthur Goetschy; Xuanchen Li; Frank Scheffold; Rachel Grange (Physical Review Research)
Nonlinear disordered media uniquely combine multiple scattering and second-harmonic generation. Here, we investigate the statistical properties of the nonlinear light generated within such media. We report super-Rayleigh statistics of the second-harmonic speckle intensity, and demonstrate that it is caused by the mesoscopic correlations arising in extreme scattering conditions. The conductance measured is exceptionally low for an isotropically scattering three-dimensional medium, enabling applications in broadband second-harmonic generation, wavefront shaping in nonlinear disordered media, and photonic computing.